Weight loss surgery for obstructive sleep apnoea with obesity in adults: a systematic review and meta-analysis protocol. Issue 8 (29th August 2018) - Dong, Zhiyong; Hong, Brian Y; Yu, Ashley M; Cathey, John; Shariful Islam, Sheikh Mohammed; Wang, Cunchuan
Abstract : Introduction: Obstructive sleep apnoea (OSA) is caused by complete or partial obstruction of the upper airway resulting in repeated episodes of interrupted or shallow breaths. OSA is associated with significant morbidity and mortality. The prevalence is estimated to range from 3% to 7% in the general population but may be much higher. Several studies show that weight loss or bariatric surgery may have a role in treating OSA. The aim of this systematic review is to assess the safety and efficacy of randomised controlled trials (RCTs) of weight loss surgery for adults with OSA and comorbid obesity. Methods and analysis: A search of the Cochrane Central Register of Controlled Trials, PubMed, EMBASE and two major Chinese biomedical databases will be performed to identify related trials published as of October 2018. This study will include RCTs, comparing different types of weight loss surgery for OSA with obesity or weight loss surgery for OSA with obesity with other upper airway surgeries. The primary outcomes that will be measured are apnoea–hypopnoea index, excess weight loss and in-hospital mortality. The secondary outcomes will include duration of hospital stay, neck circumference, reoperation, waist circumference, body mass index, Epworth Sleepiness Scale score, overt complications (eg, gastric fistula, bleeding, delayed gastric emptying, wound infection), quality of life, quality of sleep and/or functionality. The systematic review will be conducted according to the recommendations as outlined by the Cochrane collaboration. Ethics and dissemination: The systematic review and meta-analysis will include published data available online and thus ethics approval will not be required. The findings will be disseminated and published in a peer-reviewed journal. Review updates will be conducted if there is new evidence that may cause any change in review conclusions. Any changes to the study protocol will be updated in the PROSPERO trial registry accordingly. PROSPERO registration number: CRD42017081743.